CRYSTAL-STRUCTURE AND CATION STOICHIOMETRY OF SUPERCONDUCTING TL2BA2CUO6+DELTA SINGLE-CRYSTALS - Liu, R; Hughes, S; Angel, R; Hackwell, T; Mackenzie, A; Edwards, P (1992)
High quality single crystals of Tl2Ba2CuO6+δ have been obtained by a CuO self-flux method. The synthesized crystals have an average chemical composition of Tl1.85(4)Ba1.94(4)Cu1.15(2)O6+δ as determined by electron probe microanalysis (EPMA), suggesting a possible substitution of Cu for Tl. Single-crystal X-ray diffraction experiments and structure refinement show that the crystal exhibits tetragonal symmetry (space group 14/mmm), with lattice parameters a=3.8608(4) Å and c=23.1332(9) Å. Site occupancy refinements indicated completely occupied Ba and Cu sites within the structure, and a deficiency in the scattering power of the Tl site. The final structure refinement corresponds to a composition Tl1.87(2)Ba2Cu1.13(2)O6+δ, which is consistent with the EPMA results. The quality of the diffraction data allow Tl and O (which comprise the Tl2O2 layers) to be unambiguously assigned to split sites of the type x0z, as opposed to xxz sites. There is no evidence for long-range ordering of the displacements of the atoms in the Tl2O2 layers of this crystal. The as-grown single crystals have a superconducting transition temperature, Tc, of 12.4 K. The Tc of the as-grown crystals could be enhanced via low temperature annealing in a reducing atmosphere. © 1992.